Development of a real-time physician–patient communication data collection tool. Issue 4 (2nd November 2019) - Custer, Adam; Rein, Laura; Nguyen, Daniel; Wentworth, Karen; Dhamoon, Amit
Abstract : Objectives: To design a tool to assess and improve physician communication, provide physicians with personalised feedback in real time, and relate specific communication behaviours to patient experience measures. It was hypothesised that performance of fundamental communication behaviours would correlate with individual patient experience scores as measured by the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) surveys. Design: Prospective observational study. Setting: Single-centre study at a mid-sized academic tertiary medical centre. Participants: Thirteen hospitalists across 305 patient interactions were assessed in this study. Participants were recruited from three geographically cohorted adult general medicine-teaching teams on two inpatient units. Participants with cognitive impairment or who were unable to speak English were excluded from the study. Main outcome measures: Frequency of performance of 10 fundamental communication behaviours. Results: The communication behaviours of 13 hospitalists were assessed by 305 surveys: 146 observations, 106 patient reports and 52 excluded interactions. During rounds, 50% of physicians introduced themselves, 40% explained their role, 44% introduced other members of the team, 59% addressed patients by name, 58% addressed friends/family, 59% attempted to be at eye level, 41% asked permission before performing a physical examination, 40% asked if patients had questions and 20% asked if patients understood the plan of care. Several variables correlated with higher HCAHPS scores; however, addressing patients by name (r=0.60482, p=0.0492) and introducing other members of the team (r=0.87239, p=0.0234) were statistically significant. Conclusion: This study highlights the importance of effective physician–patient communication and presents a unique data collection tool to assess and improve physician communication in real time. This tool can provide physicians with personalised feedback and relate specific communication behaviours to patient experience measures to provide high-quality care and improve the patient experience.